A Multimodal End-2-End Approach to Accessible Computing - Biswas, Pradipta; Duarte, Carlos; Langdon, Patrick; Almeida, Luis.; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2015)
This book illustrates how Interactive Systems can help elderly and disabled populations engage with the world around them by finding methods of overcoming the difficulties these communities face when using such systems by presenting the latest in state-of-the-art technology and providing a vision for accessibility for the near future. The challenges faced by accessibility practitioners are discussed and the different phases of delivering accessible products and services are explored. A collection of eminent researchers from around the world cover topics on developing and standardizing user models for inclusive design, adaptable multimodal system development for digital TV and ubiquitous devices, presenting research on intelligent voice recognition, adaptable pointing, browsing and navigation, and affect and gesture recognition. The research not only focuses on how these can be hugely beneficial to primary users, but often finding useful applications for their able-bodied counterparts. For this new edition, new chapters have been added focusing on the latest developments in games for the visually impaired, inclusive interfaces for the agricultural industry in India and technologies to improve accessibility in broadcasting in Japan. A Multimodal End-2-End Approach to Accessible Computing will be an invaluable resource for both researchers and practitioners alike.
Foreword -- Preface -- Part I – Design -- What Technology Can and Cannot Offer an Ageing Population: Current Situation and Future Approach -- Survey on Inclusive Human Machine Interaction Issues in India -- Developing an Interactive TV for the Elderly and Impaired: An Inclusive Design Strategy -- Designing TV Interaction for the Elderly – A Case Study of the Design for All Approach -- Inclusive User Modelling and Simulation -- Part II – Development -- Intelligent Interaction in Accessible Applications -- Interaction Techniques for Users with Severe Motor-Impairment -- Embodied Virtual Agents as a Means to Foster E-Inclusion of Older People -- Building an Adaptive Multimodal Framework for Resource Constrained Systems -- A New Agricultural Advisory System- Personalized Interfaces And Interactions -- Audio Games: Investigation of the Potential Through Prototype Development -- Part III – Maintenance -- R&D for Accessible Broadcasting in Japan -- Evaluating the Accessibility of Adaptive TV based Web Applications -- Television Accessibility in China -- An Interoperable and Inclusive User Modelling concept for Simulation and Adaptation -- Standardization of Audiovisual Media Accessibility – From Vision to Reality -- Author Index. .
Keywords: User interfaces (Computer systems).; Application software; User Interfaces and Human Computer Interaction; Computer Appl. in Social and Behavioral Sciences